Redesain Website Smpn 2 Bangorejo Menggunakan Metode User Centered Design Sebagai Media Promosi - Putri, Andini Nabela; Haq, Endi Sailul; Umam, Khoirul (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
The dissemination of information today is largely conducted through websites, making it easier for everyone to access information anywhere with the internet. Various formal institutions utilize websites for marketing, information, education, communication, and promotion. One such utilization is the website of SMPN 2 Bangorejo, which aims to attract prospective new students to enroll at SMPN 2 Bangorejo. However, the promotion through the website has not been optimal, as interviews conducted with 6th-grade elementary school students revealed that they were unaware of the SMPN 2 Bangorejo website. A presentation of the school website was then conducted for the students, and it was found that the 6th-grade students encountered several difficulties in navigating the website. This study aims to provide design recommendations for the SMPN 2 Bangorejo website. An initial survey calculated using the System Usability Scale (SUS) method yielded a score of 49.71 with a